2013
DOI: 10.1016/j.ophtha.2012.07.066
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Inner Retinal Layers in Patients with Multiple Sclerosis or Neuromyelitis Optica Using Optical Coherence Tomography

Abstract: Purpose To evaluate the thickness of the inner retinal layers in the macula using frequency domain-optical coherence tomography (fd-OCT) in patients with demyelinating diseases. Design Cross sectional study Participants 301 eyes of 176 subjects were evaluated. Subjects were divided in 5 different groups: controls, neuromyelitis optica (NMO), longitudinally extensive transverse myelitis (LETM), multiple sclerosis with (MS-ON) and without (MS non-ON) history of optic neuritis, respectively. Methods The ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
0
14

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(97 citation statements)
references
References 37 publications
8
74
0
14
Order By: Relevance
“…Damage to optic nerves in NMO is associated with retinal injury, including thinning of the inner retinal layers (IRLs) and axonal damage (20). Therefore, we also evaluated optic nerve involvement in recipients of encephalitogenic Th17-polarized AQP4-specific T cells by serial OCT.…”
Section: Aqp4-specific T Cells From Aqp4mentioning
confidence: 99%
“…Damage to optic nerves in NMO is associated with retinal injury, including thinning of the inner retinal layers (IRLs) and axonal damage (20). Therefore, we also evaluated optic nerve involvement in recipients of encephalitogenic Th17-polarized AQP4-specific T cells by serial OCT.…”
Section: Aqp4-specific T Cells From Aqp4mentioning
confidence: 99%
“…Oberwahrenbrock et al 20 reported that eyes of MS patients without a previous ON showed a significant reduction of RNFL thickness compared with healthy controls. Fernandes et al 21 showed that RNFL thickness was significantly reduced in patients with MS, either with or without ON. Similarly, in our study, RNFL was significantly thinner in MS patients than controls and in MS group, the difference in RNFL between eyes with or without ON was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] In addition, it has been suggested that OCT can help differentiate demyelinating diseases, and OCT findings can be long-term prognostic factors on the basis of the severity of axonal loss. 10,11 OPN has been reported as a type of idiopathic orbital inflammatory disease and the diagnosis of OPN is most commonly based on the magnetic resonance image findings, along with the clinical characteristics. 2,12 Neuro imaging in OPN patient typically shows a characteristic pattern of enhancement around the optic nerve, like tram-track on axial views and doughnut on coronal views.…”
Section: Discussionmentioning
confidence: 99%